The possible uses of RTN-solutions for markup works on construction - Бурак, К.; Лиско, Б.; Burak, K.; Lysko, B. (Видавництво Львівської політехніки, 2018)
Розроблення практичних рекомендацій для винесення головних осей будівель (осей симетрії) з використання RTN методики GNSS-вимірів та забезпечення додаткового контролю розмічувальних робіт з використанням електронного тахеометра. Методика. Для дослідження точності пропонованих рішень виконані дослідження, в тому числі і експериментальні в умовах будівельного майданчика, з розмічування осей від двох базових ліній, попередньо винесених GNSS-приймачем так, щоб вони збігалися з осями x і y генерального плану об’єкта. Наукова новизна та практична значущість. В роботі пропонується замість суцільної будівельної сітки виносити відразу головні осі будівель, а від них безпосередньо, за допомогою електронного тахеометра, розвивати розмічувальні мережі споруди. Метод дає можливість відмовитись від побудови класичної будівельної сітки, замінивши опорну геодезичну мережу двома базовими лініями (мінімум 4 опорні точки), які закріпляють положення осей координат генерального плану та додатково контролювати розмічування осей електронним тахеометром способом від базової лінії, використовуючи для контролю значення віддалей між точками базових ліній, виміряне методом RTN.

Creating the practical recommendations for measuring the main buildings axes (symmetry axes) with the help of RTN method of GNSS measurements and providing the additional control over the marking works with electronic total station. Methodology. To ensure the accuracy of the recommended methods, the studies, including experimental ones, with measuring the axes from two basis lines are taken by GNSS receiver in such a way to coincide with the x and y axes of the object’s general plan. To minimize the sporadic errors and increase the accuracy of obtained results, the investigation was made on the inherent basis, which allows the forced centering of tools. The special aspect of this basis is that it is situated very close to the permanent station (10 km). This factor substantially compensates the systematic errors in the results of the relative measurements. Results: Results of the study are: it was established that when setting the fixing baseline with the dual-frequency GNSS receiver in the way its points coincide with the main axes of construction netting and the following marking of all the elements of the construction site toward this baseline, the required accuracy is provided, e.g. mutual location of points of main, basic, and detailed axes, and in some cases fitting axes as well. Scientific novelty and practical significance. The method, described in the work, involves measuring the main building axes instead of the contiguous construction netting. Then, with the help of the electronic tacheometer, we can extend the measuring nettings of the building. This method allows to avoid building the basic construction netting by changing the mounting geodesic netting with the two basic lines (with at least 4 mounting points), that fix the position of the coordinates axes of the general plan and additionally control the axes marking with the electronic tacheometer from the basic line by using the distances value between the basic lines points, measured with the RTN method.
Можливості використання RTN-рішень для розмічувальних робіт на будівництві
Keywords: GNSS; TPS; RTN-вимір; розпланувальні роботи; електронний тахеометр; GNSS; TPS; RTN measurement; planning works; electronic total station; 528.3